The ACLY inhibitor SB204990 does not alter lysine histone acetylation in mouse liver - Castillo Peña, Alejandro; Sola García, Alejandro; Cáliz Molina, María de los Ángeles; Martín-Montalvo, Alejandro; Martín-Montalvo, Alejandro (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2021)
Motivation: Acetyl-coenzyme A is a fundamental component of cell metabolism, which plays a role in energy production, macromolecular biosynthesis and protein modification. Within the mitocondria, acetyl-coenzyme A condensation with oxaloacetate generates citrate, which can be exported to the cytosol, where is cleavaged by ATP-citrate lyase (ACLY), producing again acetyl-coenzyme A and oxaloacetate. In the nucleus and the cytoplasm acetyl-coenzyme A is used for important cellular functions such as histone acetylation or fatty acid synthesis. Silencing or inhibition of ACLY impairs tumor growth and produces blood lipid-lowering effects. Moreover, ACLY inhibitors are reasonably well tolerated in adult animals. Thus, ACLY inhibition could represent a therapeutic opportunity for the treatment of cancer and metabolic diseases, making its mechanistic understanding a promising field of study. Histone acetylation is a molecular mechanism that controls gene expression. Previous data has shown that global histone acetylation is latered in ACLY-deficient cell lines. Herein, we evaluated whether beneficial metabolic effects observed in mice exposed for 16 weeks to a pharmacological inhibitor of the ACLY are associated to modulations in histone acetylation in liver tissue lysates. Methods: An histone acid extraction wass conducted using the livers of mice exposed to 4 experimental conditions: standard diet, standard diet + SB (250 mg/Kg of food), high fat diet and high fat diet + SB (250 mg/Kg of food). Samples were procesed and western blots using specific antibodies of several histone-lysines were performed to evaluate potential modulations on histone acetylation levels between. Results and conclusions: Current data indicates that acetylation levels of H3K9, H3K14, H3K18, H3K56, H4K5, H4K8 are not significantly altered in the different experimental conditions. These results indicate that beneficial effects produced by ACLY inhibition are not caused by changes in histone acetylation in the liver.